Nitrogen-sulfur double-doped PtM / C catalyst as well as synthesis method and application thereof

Through the synthesis method of nitrogen and sulfur double-doped PtM/C catalyst, the problem of unsatisfactory particle size and poor stability of noble metal-based alloy catalysts in the prior art was solved, and a catalyst with high electrochemical ORR performance and stability was prepared, suitable for fuel Battery application, and environmentally friendly process and suitable for large-scale production.

CN119400883APending Publication Date: 2025-02-07GEM CO LTD +1

Patent Information

Application Number
CN202411517408.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the particle size of the noble metal-based alloy catalyst prepared by the non-organic solvent system is not ideal enough, and it is prone to agglomeration. The stability of the noble metal-based alloy is poor and is not suitable for actual fuel cell applications.

Method used

Using the PtM/C catalyst synthesis method with nitrogen and sulfur double-doped, the organic ligand, noble metal Pt precursor, M precursor and carbon support are mixed with a non-organic solvent, and the first calcination is performed after drying to obtain nitrogen and sulfur double-doped PtM/C catalyst. This method allows S and N elements to be doped in the particles, inhibiting the agglomeration of nanoparticles and improving the catalyst performance.

Benefits of technology

The prepared nitrogen-sulphur double-doped PtM/C catalyst has high electrochemical ORR performance and stability, and its performance is better than that of commercial platinum carbon/platinum-cobalt binary alloys. Its activity and stability meet the DOE2025 target, and its process is simple and safe. , suitable for mass production and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400883A_ABST
    Figure CN119400883A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-sulfur double-doped PtM / C catalyst as well as a synthesis method and application thereof. The synthesis method comprises the following steps: 1) mixing an organic ligand, a noble metal Pt precursor, an M precursor and a carbon carrier with a non-organic solvent, and drying to obtain a catalyst precursor; wherein M in the M precursor is a transition metal element, the organic ligand comprises doping elements, and the doping elements comprise N and S; and 2) carrying out first calcination on the catalyst precursor in a reducing atmosphere to obtain the nitrogen-sulfur double-doped PtM / C catalyst. According to the method disclosed by the invention, the organic ligand, the noble metal Pt precursor, the M precursor and the carbon carrier are mixed with the non-organic solvent, so that the agglomeration of nanoparticles can be better inhibited, and the performance of the catalyst is improved. In addition, double doping of N and S elements can achieve a synergistic effect. No organic solvent is needed, no organic waste liquid is generated, and the method is environment-friendly and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells and relates to a nitrogen-sulfur dual-doped PtM / C catalyst and a synthesis method and application thereof. Background Art

[0002] As a clean, efficient and sustainable energy source, hydrogen energy is one of the important channels for countries to achieve low-carbon goals. Proton exchange membrane fuel cell (PEMFC) is the core device for realizing hydrogen energy utilization. It is a zero-carbon emission power generation device that converts chemical energy into electrical energy. The process of converting chemical energy into electrical energy is inseparable from catalysts. Among them, precious metal platinum catalysts are considered to be catalysts with excellent oxygen reduction reaction performance. At the same time, platinum carbon is also the most widely used catalyst. Due to the high price of platinum and the lack of resources, reducing the amount of platinum in the catalyst has become a top priority. Among them, platinum alloying has been proven to be an effective means to reduce the amount of platinum under the premise of high performance of fuel cells. In addition, platinum alloy catalysts (PtM) can also greatly improve the catalytic activity of the oxygen reduction reaction at the cathode of fuel cells. Based on this, the development of platinum alloy electrocatalysts is imminent.

[0003] CN116422342B discloses a solvent thermal reduction synthesis method for a platinum alloy catalyst, by heating a mixed solution of different metal salts, a carrier and a reducing substance, separating the solid and subjecting it to high temperature heat treatment to obtain different platinum alloy catalysts. Although this method has high universality and can synthesize small-particle catalysts, it is necessary to use an organic solvent, which will produce organic waste liquid, which is harmful to the environment and is not suitable for mass production. CN111224116A discloses a ball milling synthesis method for a metal nitrogen-carbon catalyst, which does not require the introduction of an organic solution as a solvent during the synthesis process and is environmentally friendly, but the catalyst prepared by the ball milling method is prone to large particle size. Moreover, although the method additionally introduces a nitrogen source material, it overcomes the problem of large particle size to a certain extent, and synthesizes a highly active catalyst at the same time. However, the size of the synthesized catalyst is still not ideal by introducing a nitrogen source alone, mainly because: nitrogen has a limited agglomeration effect on platinum alloy particles.

[0004] At present, most of the noble metal-based alloy catalysts prepared by the non-organic solvent system proposed in the prior art have less than ideal particle size, are prone to agglomeration, and the stability of the noble metal-based alloys is poor, making them unsuitable for actual fuel cell applications.

[0005] In view of this, providing an environmentally friendly synthesis method to synthesize precious metal-based alloy catalysts with suitable particle size and excellent ORR performance without using organic solvents is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a nitrogen-sulfur dual-doped PtM / C catalyst and a synthesis method and application thereof.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst, the method comprising the following steps:

[0009] (1) mixing an organic ligand, a noble metal Pt precursor, an M precursor and a carbon support with a non-organic solvent, and drying to obtain a catalyst precursor;

[0010] Wherein, M in the M precursor is a transition metal element, and the organic ligand includes a doping element, and the doping element includes N and S;

[0011] (2) The catalyst precursor is subjected to a first calcination in a reducing atmosphere to obtain a nitrogen-sulfur dual-doped PtM / C catalyst.

[0012] The method of the present invention is to mix an organic ligand, a noble metal Pt precursor, an M precursor and a carbon carrier with a non-organic solvent, so that the organic ligand is added together with the noble metal Pt precursor, the M precursor and the carbon carrier during the impregnation process, so as to achieve coordination between the ligand and the noble metal Pt particles and the transition metal particles, so that the S and N elements in the ligand are doped into the particles, rather than directly doping N and S in advance on the carbon carrier; this doping method can better inhibit the agglomeration of nanoparticles and improve the performance of the catalyst. Moreover, both N and S elements participate in the coordination, realize double doping and play a synergistic role, wherein the N element can regulate the ORR performance of the catalyst, reduce the surface energy of the noble metal Pt and M atoms on the surface of the nanoparticles, and inhibit the dissolution of the noble metal atoms from the nanoparticles during the ORR reaction, and the S element can effectively inhibit the agglomeration of the noble metal nanoparticles, so that the particle size is controllable, and a noble metal-based alloy catalyst with a smaller particle size can be prepared, and the particles have a high degree of dispersibility and good stability on the carbon carrier, which solves the disadvantages of the catalyst only doped with N or S elements.

[0013] The nitrogen-sulfur dual-doped PtM / C catalyst prepared by the method of the present invention has high electrochemical ORR performance and stability, meeting future commercialization goals.

[0014] The synthesis process of the present invention is mainly an impregnation method, which is simple and safe, and is easy to mass produce compared with other processes. Moreover, the method uses a non-organic solvent system to prepare the catalyst. Compared with the mainstream solvent thermal reduction method, the method of the present invention does not require the use of organic solvents, does not produce organic waste liquid, is environmentally friendly, and is suitable for large-scale production.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] Preferably, the organic ligand in step (1) includes at least one of pyroglutamic acid, sodium pyroglutamate, histidine, valine, aspartic acid, sodium aspartate, threonine, theanine, serine, citrulline, glycine, sodium glycinate, glutamic acid, sodium glutamate, sodium thioglycolate, thiolactic acid, cysteine, hexylthioamide, pentylthioamide, dithiothreitol and 1-thioglycerol, preferably a small molecule organic ligand. In the present invention, when selecting a specific substance as an organic ligand, a single type can be selected, or a combination of two or more can be selected. It should be noted that it should be ensured that the N element and the S element are provided at the same time. Exemplarily, the amino group in the substance can provide the N element, and the sulfur group in the substance can provide the S element.

[0017] In the present invention, small molecule organic ligand refers to an organic ligand with a carbon chain length of less than 10 carbon atoms.

[0018] Preferably, the small molecule organic ligand includes at least one of sodium glycine, sodium glutamate, cysteine, sodium thioglycolate and thiolactic acid.

[0019] In the present invention, the organic ligand should provide both N and S elements. Specifically, the N and S elements may come from the same organic ligand or from several organic ligands respectively, which is not specifically limited in the present invention.

[0020] Preferably, the molar ratio of the organic ligand in step (1) to the noble metal element in the noble metal Pt precursor is 1:(0.5-2), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:1, 1:1.2, 1:1.3, 1:1.4, 1:1.6, 1:1.8 or 1:2, etc., preferably 1:(1-1.5).

[0021] Preferably, the non-organic solvent in step (1) is water.

[0022] Preferably, the noble metal Pt precursor in step (1) is a Pt precursor.

[0023] Preferably, the Pt precursor includes at least one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride, tetraammine platinum nitrate and potassium hexaiodideplatinate.

[0024] Preferably, the transition metal element M is selected from at least one of Fe, Co, Ni, Cu and Zn.

[0025] Preferably, the M precursor in step (1) includes at least one of ferric nitrate, ferric sulfate, ferric chloride, cobalt nitrate, cobalt sulfate, cobalt chloride, nickel nitrate, nickel sulfate, nickel chloride, copper nitrate, copper sulfate, copper chloride zinc nitrate, zinc sulfate and zinc chloride.

[0026] Preferably, the molar ratio of the noble metal Pt to the transition metal M is (1.2-1):1, for example, it can be 1.2:1, 1.15:1, 1.1:1, 1.05:1 or 1:1.

[0027] Preferably, the mixing in step (1) is carried out under stirring, and the mixing time is 3-48 h, for example, it can be 3 h, 5 h, 7 h, 8 h, 10 h, 12 h, 14 h, 15 h, 16 h, 18 h, 20 h, 22 h, 24 h, 25 h, 28 h, 30 h, 33 h, 36 h, 38 h, 40 h, 45 h or 48 h, etc., preferably 10-18 h.

[0028] In one embodiment, the stirring is performed at room temperature.

[0029] In the present invention, normal temperature refers to 20-25°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C or 25°C.

[0030] Preferably, the drying method in step (1) is: removing water by rotary evaporation and then performing vacuum drying.

[0031] The present invention does not specifically limit the type of the carbon carrier in step (1), including but not limited to at least one of EC300-JD, EC600-JD, XC-72 and BP2000.

[0032] As a preferred technical scheme for the synthesis method of the nitrogen-sulfur dual-doped PtM / C catalyst of the present invention, the time of the first calcination in step (2) is 2-10h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.

[0033] Preferably, the heating rate of the first calcination in step (2) is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.

[0034] Preferably, the temperature of the first calcination in step (2) is 600-950°C, for example, it can be 600°C, 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C, 900°C or 950°C, etc.

[0035] Preferably, the gas in the reducing atmosphere in step (2) includes reducing gas and protective gas, and the volume concentration of the reducing gas is 2-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0036] The present invention does not specifically limit the types of reducing gas and protective gas. For example, the reducing gas may be H2, and the protective gas may be at least one of Ar, N2 or He.

[0037] As a preferred technical solution of the synthesis method of the nitrogen-sulfur dual-doped PtM / C catalyst of the present invention, the synthesis method further comprises performing step (3) after the first calcination:

[0038] The product obtained by the first calcination is acid-washed, dried, and then subjected to a second calcination in a reducing atmosphere to obtain a doped PtM / C catalyst.

[0039] Preferably, in step (3), the acid used for pickling includes at least one of perchloric acid, sulfuric acid, nitric acid and acetic acid.

[0040] Preferably, in step (3), the concentration of the acid used for pickling is 0.1-0.5M, for example, it can be 0.1M, 0.2M, 0.3M, 0.4M or 0.5M.

[0041] Preferably, in step (3), the pickling temperature is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0042] Preferably, in step (3), the pickling time is 0.5-4 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0043] Preferably, in step (3), the second calcination time is 0.5-4 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0044] Preferably, in step (3), the heating rate of the second calcination is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.

[0045] Preferably, in step (3), the temperature of the second calcination is 200-500°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C.

[0046] Preferably, in step (3), the gas in the reducing atmosphere includes reducing gas and protective gas, and the volume concentration of the reducing gas is 2-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0047] As a preferred technical solution of the synthesis method of the nitrogen-sulfur dual-doped PtM / C catalyst of the present invention, the method comprises the following steps:

[0048] Step 1, adding an organic ligand, a platinum precursor, an M precursor and a carbon carrier to deionized water in sequence and performing ultrasonic dispersion to obtain a mixed solution;

[0049] Step 2, stirring the mixed solution of step 1 at room temperature until it is fully mixed, rotary evaporating the mixed solution and drying it in a vacuum drying oven to prepare a catalyst precursor;

[0050] Step 3, calcining the catalyst precursor at 600-950° C. in a reducing atmosphere, during which a reduction reaction occurs;

[0051] Step 4: According to the demand, the calcined product obtained in step 3 is dispersed in an acid solution of a certain concentration for acid washing. After filtering and drying, the obtained solid is calcined at 200-500° C. in a reducing atmosphere to obtain a nitrogen-sulfur dual-doped PtM / C catalyst.

[0052] In a second aspect, the present invention provides a nitrogen-sulfur dual-doped PtM / C catalyst prepared by the method described in the first aspect, wherein the nitrogen-sulfur dual-doped PtM / C catalyst comprises a carbon carrier and a platinum-based binary alloy loaded on the carbon carrier, wherein the platinum-based binary alloy is an intermetallic ordered alloy formed by a precious metal element Pt and a transition metal element M, and the platinum-based binary alloy is doped with doping elements, wherein the doping elements include N and S.

[0053] In the nitrogen-sulfur dual-doped PtM / C catalyst prepared by the method of the present invention, the noble metal element Pt and the transition metal element M form an ordered intermetallic alloy, the nanoparticles of which are highly dispersed on the surface of the carbon carrier, with a small average particle size, and the nanoparticles have a high specific surface area and electrochemical active area.

[0054] The nitrogen-sulfur dual-doped PtM / C catalyst of the present invention has high electrochemical ORR performance and stability. Its performance is better than that of commercial platinum-carbon / platinum-cobalt binary alloy, and its activity and stability meet the DOE2025 target.

[0055] Preferably, the mass proportion of the precious metal element Pt in the doped PtM / C catalyst is 10-50wt%, for example, it can be 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, 33wt%, 36wt%, 40wt%, 42wt%, 44wt%, 46wt%, 48wt% or 50wt%, etc., preferably 25-35wt%.

[0056] Preferably, the mass proportion of the transition metal element M in the doped PtM / C catalyst is 3-30wt%, for example, it can be 3wt%, 5wt%, 7wt%, 8wt%, 10wt%, 12wt%, 15wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%, etc., preferably 6-10wt%.

[0057] Preferably, the transition metal element M is selected from at least one of Fe, Co, Ni, Cu and Zn.

[0058] Preferably, the mass proportion of the doping element in the nitrogen-sulfur dual-doped PtM / C catalyst is 0.1-5wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.6wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., preferably 0.5-1%.

[0059] Preferably, the doping element is uniformly doped in the crystal lattice of the binary alloy nanoparticles in the form of single atoms.

[0060] Preferably, the average particle size of the binary alloy is 3-8 nm, for example, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm or 8 nm, etc. If the average particle size of the binary alloy is too large or too small, it will cause a loss in fuel cell performance.

[0061] In a third aspect, the present invention provides a fuel cell, wherein the fuel cell comprises the nitrogen-sulfur dual-doped PtM / C catalyst described in the second aspect.

[0062] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] (1) The method of the present invention is to mix the organic ligand, the noble metal Pt precursor, the M precursor and the carbon carrier with the non-organic solvent, so that the organic ligand is added together with the noble metal Pt precursor, the M precursor and the carbon carrier during the impregnation process, so as to achieve the coordination between the ligand and the noble metal (such as Pt) particles and the transition metal particles, so that the S and N elements in the ligand are doped into the particles, rather than directly doping N and S in advance on the carbon carrier; this doping method can better inhibit the agglomeration of nanoparticles and improve the catalyst performance. Moreover, both N and S elements participate in the coordination, realize double doping and play a synergistic role, wherein the N element can regulate the ORR performance of the catalyst, reduce the surface energy of the noble metal (such as Pt) and M atoms on the surface of the nanoparticles, and inhibit the dissolution of the noble metal atoms from the nanoparticles during the ORR reaction, and the S element can effectively inhibit the agglomeration of the noble metal nanoparticles, so that the particle size is controllable, and a noble metal-based alloy catalyst with a smaller particle size can be prepared, and the particles have high dispersibility and good stability on the carbon carrier, which solves the disadvantages of the catalyst doped with only N element or S element.

[0065] (2) The nitrogen-sulfur dual-doped PtM / C catalyst prepared by the method of the present invention has high electrochemical ORR performance and stability, and its performance is better than that of commercial platinum-carbon / platinum-cobalt binary alloys. The activity and stability meet the DOE2025 target.

[0066] (3) The synthesis process of the present invention is mainly an impregnation method, which is simple and safe, and is easy to mass produce compared with other processes. Moreover, the method uses a non-organic solvent system to prepare the catalyst. Compared with the mainstream solvent thermal reduction method, the method of the present invention does not require the use of organic solvents, does not produce organic waste liquid, is environmentally friendly, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is the XRD pattern of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1.

[0068] Figure 2 TEM image of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1.

[0069] Figure 3 The activity comparison chart of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1, commercial Pt / C (Comparative Example 5), and PtCo / C (Comparative Example 6).

[0070] Figure 4 ORR forward scanning polarization curves of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1 in an O2-saturated 0.1M HClO4 solution for initial and 30,000 cycles of stability testing.

[0071] Figure 5Cyclic voltammetry curves of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1 at the beginning and after 30,000 cycles of stability testing.

[0072] Fig. 6A and Figure 6B They are the XRD and ORR forward scanning polarization curves of Control Example 1, respectively.

[0073] Fig. 7A and Figure 7B They are the XRD and ORR forward scanning polarization curves of Control Example 2, respectively.

[0074] Fig. 8A and Figure 8B They are the XRD and ORR forward scanning polarization curves of Control Example 3 respectively.

[0075] Fig. 9A and Fig. 9B They are the XRD and ORR forward scanning polarization curves of Control Example 4, respectively. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0077] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0078] Example 1

[0079] This embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (hereinafter referred to as a binary N,S-PtCo / C ordered intermetallic alloy catalyst), comprising the following steps:

[0080] (1) adding an organic small molecule ligand (cysteine), chloroplatinic acid, cobalt chloride and a carbon carrier (EC300-JD) to deionized water in sequence, wherein the molar ratio of the organic small molecule ligand to chloroplatinic acid is 1:1, and performing ultrasound until the carbon carrier is dispersed to obtain a mixed solution;

[0081] (2) stirring the dispersed mixed solution at room temperature for 12 hours, rotary evaporating the uniformly dispersed solution to remove water, and placing it under vacuum drying at 80° C. to obtain a N,S-PtCo / C intermetallic ordered alloy catalyst precursor;

[0082] (3) The N, S-PtCo / C intermetallic ordered alloy catalyst precursor was heated to 900°C at a rate of 5°C / min under 5% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 5%), and heat treated for 2h to obtain a N, S-PtCo / C intermetallic ordered alloy.

[0083] (4) The N,S-PtCo / C intermetallic ordered alloy is placed in a 0.1M perchloric acid solution, stirred evenly, and then heated to 60°C for acid washing for 1 hour to remove part of the cobalt on the surface of the nanoparticles. After the reaction is completed, it is washed with deionized water until neutral and then dried. Finally, it is placed at 400°C and 5% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 5%) for heat treatment for 0.5h to obtain N,S-PtCo / C nitrogen-sulfur dual-doped PtM / C catalyst, that is, nitrogen-sulfur dual-doped PtM / C catalyst.

[0084] Example 2

[0085] This embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (referred to as a binary N,S-PtNi / C intermetallic ordered alloy catalyst). The synthesis method of this embodiment 2 is consistent with that of embodiment 1, except that the cobalt chloride in step (2) is replaced by nickel chloride.

[0086] Example 3

[0087] The present embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (referred to as a binary N,S-PtCo / C metal ordered alloy catalyst). The synthesis method of the present embodiment 3 is consistent with that of the embodiment 1, except that the organic small molecule ligand cysteine ​​in step (1) is replaced by a mixture of sodium glycine (NH2CH2COONa) and sodium thioglycolate, and the mass ratio of sodium glycine to sodium thioglycolate is 1:1.2.

[0088] Example 4

[0089] The present embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (referred to as a binary N,S-PtFe / C intermetallic ordered alloy catalyst). The synthesis method of the present embodiment 4 is consistent with that of the embodiment 1, except that the cobalt chloride in step (1) is replaced by ferric sulfate, and the organic small molecule ligand cysteine ​​is replaced by a mixture of thiolactic acid (C3H6O2S) and sodium glutamate (C5H8NNaO4), and the mass ratio of thiolactic acid to sodium glutamate is 1:1.6.

[0090] Example 5

[0091] This embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (referred to as a binary N,S-PtCo / C intermetallic ordered alloy catalyst). The synthesis method of this embodiment 4 is consistent with that of embodiment 1, except that the carbon carrier EC300-JD in step (1) is replaced with XC-72.

[0092] Example 6

[0093] This embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (hereinafter referred to as a binary N,S-PtCo / C ordered intermetallic alloy catalyst), comprising the following steps:

[0094] (1) adding an organic small molecule ligand (cysteine), platinum tetrachloride, cobalt chloride and a carbon support (BP2000) in deionized water in sequence, wherein the molar ratio of the organic small molecule ligand to chloroplatinic acid is 1:1.5, and performing ultrasound until the carbon support is dispersed to obtain a mixed solution;

[0095] (2) stirring the dispersed mixed solution at room temperature for 18 hours, rotary evaporating the uniformly dispersed solution to remove water, and placing it under vacuum drying at 80° C. to obtain a N,S-PtCo / C intermetallic ordered alloy catalyst precursor;

[0096] (3) The N, S-PtCo / C intermetallic ordered alloy catalyst precursor was heated to 700°C at a rate of 2°C / min under 3% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 3%), and heat treated for 8 hours to obtain a N, S-PtCo / C intermetallic ordered alloy.

[0097] (4) The N,S-PtCo / C intermetallic ordered alloy is placed in a 0.3M perchloric acid solution, stirred evenly, and then heated to 50°C for acid washing for 3 hours to remove part of the cobalt on the surface of the nanoparticles. After the reaction is completed, it is washed with deionized water until neutral and then dried. Finally, it is placed at 300°C and 5% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 5%) for heat treatment for 3 hours to obtain N,S-PtCo / C nitrogen-sulfur dual-doped PtM / C catalyst, that is, nitrogen-sulfur dual-doped PtM / C catalyst.

[0098] Example 7

[0099] This embodiment provides a method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst (hereinafter referred to as a binary N,S-PtCo / C ordered intermetallic alloy catalyst), comprising the following steps:

[0100] (1) adding an organic small molecule ligand (cysteine), potassium chloroplatinite, cobalt chloride and a carbon carrier (EC300-JD) to deionized water in sequence, wherein the molar ratio of the organic small molecule ligand to chloroplatinic acid is 1:1.2, and performing ultrasound until the carbon carrier is dispersed to obtain a mixed solution;

[0101] (2) stirring the dispersed mixed solution at room temperature for 10 hours, rotary evaporating the uniformly dispersed solution to remove water, and vacuum drying the solution at 85° C. to obtain a N,S-PtCo / C intermetallic ordered alloy catalyst precursor;

[0102] (3) The N, S-PtCo / C intermetallic ordered alloy catalyst precursor was heated to 600°C at a rate of 10°C / min under 10% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 10%), and heat treated for 10 hours to obtain a N, S-PtCo / C intermetallic ordered alloy.

[0103] (4) The N,S-PtCo / C intermetallic ordered alloy is placed in a 0.5M perchloric acid solution, stirred evenly, and then heated to 80°C for acid washing for 0.5h to remove part of the cobalt on the surface of the nanoparticles. After the reaction is completed, it is washed with deionized water until neutral and then dried. Finally, it is placed at 500°C and 10% hydrogen-argon mixed gas (a mixture of hydrogen and argon, in which the volume proportion of hydrogen is 10%) for heat treatment for 0.5h to obtain a N,S-PtCo / C nitrogen-sulfur dual-doped PtM / C catalyst, that is, a nitrogen-sulfur dual-doped PtM / C catalyst.

[0104] Example 8

[0105] The synthesis method of Example 8 is consistent with that of Example 1, except that the molar ratio of the organic small molecule ligand to chloroplatinic acid in step (1) is adjusted to 1:0.5.

[0106] Example 9

[0107] The synthesis method of this Example 9 is consistent with that of Example 1, except that the molar ratio of the organic small molecule ligand to chloroplatinic acid in step (1) is adjusted to 1:2.

[0108] Example 10

[0109] The synthesis method of this Example 10 is consistent with that of Example 1, except that the organic small molecule ligand cysteine ​​in step (1) is replaced by a mixture of pyroglutamic acid and hexanethioamide, and the amounts of pyroglutamic acid and hexanethioamide satisfy that the molar ratio of N to S is consistent with the molar ratio of N to S in cysteine ​​in Example 1.

[0110] Comparative Example 1

[0111] The synthesis method of this comparative example is consistent with that of Example 1, except that the cysteine ​​incorporated in step (1) is eliminated, that is, no organic small molecule ligand is doped.

[0112] Comparative Example 2

[0113] The synthesis method of this comparative example is consistent with that of Example 1, and the only changed step is that the organic small molecule ligand incorporated in step (1) is sodium glutamate, that is, only the organic small molecule ligand containing the N element is doped.

[0114] Comparative Example 3

[0115] The synthesis method of this comparative example is consistent with that of Example 1, and the only changed step is that the organic small molecule ligand incorporated in step (1) is sodium thioglycolate, that is, only the organic small molecule ligand containing the S element is doped.

[0116] Comparative Example 4

[0117] The synthesis method of this comparative example is basically the same as that of Example 1, except that the position of the organic small molecule ligand is changed, and the EC300-JD added in step (1) is replaced with EC300-JD doped with cysteine ​​in advance, and the cysteine ​​added separately in step (1) is cancelled. The specific method of incorporating cysteine ​​into EC300-JD is as follows: cysteine ​​and EC300-JD are ground in a mortar for 20 minutes, and then calcined at 600°C for 2 hours under the condition of 5% hydrogen-argon mixed gas (a mixture of hydrogen and argon, wherein the volume proportion of hydrogen is 5%).

[0118] Comparative Example 5

[0119] This comparative example 5 is a commercial Pt / C catalyst.

[0120] Comparative Example 6

[0121] This comparative example 6 is a commercial PtCo / C catalyst.

[0122] The average particle size and element content of the nanoparticles of the catalysts of Examples 1-10 and Comparative Examples 1-4 are shown in Table 1:

[0123] Table 1

[0124]

[0125]

[0126] As shown in Table 1 above, the synergistic effect of N and S elements and their doping between particles can inhibit the migration and agglomeration of nanoparticles during the heat treatment process, so that an alloy catalyst with a smaller particle size is finally obtained.

[0127] By comparing Example 1 with Examples 8-9, it can be seen that when there are more ligands, over-coordination will occur, which will slow down the nucleation rate of the alloy under low temperature conditions during heat treatment, and the nucleation will be incomplete, and more Oswald ripening will occur in the high temperature zone, resulting in uneven particle size and the production of more large particles; when there are fewer ligands, their coordination ability is weak, the nucleation and growth rates of the alloy are too fast during the heating process, and the particle size is relatively large.

[0128] The particle size of Example 10 is more appropriate, and the particle size of Examples 8-9 is not too large, indicating that the influence of the type of nitrogen / sulfur-containing ligand on the catalyst particle size is not as great as the input ratio of the ligand to the metal precursor. However, the chemical structures of different ligands and the coordination environments after combining with Pt are different, resulting in different effects on the catalyst particle size, performance, etc. when different ligands are selected, but the degree of the influence is small.

[0129] The following tests were performed on the nitrogen-sulfur dual-doped PtM / C catalysts of Examples 1-10 and the catalysts of Comparative Examples 1-6:

[0130] (1) X-ray diffraction (XRD) test: The powder sample was evenly flattened in the groove of the quartz plate and placed in the test instrument. The tube voltage and tube current of the instrument were adjusted to 40 kV and 15 mA respectively. The test angle was 10°-90° and the scanning speed was 5° / min.

[0131] (2) Transmission electron microscopy (TEM) test

[0132] (3) Rotating disk electrode (RDE) test: 3 mg of catalyst was dispersed in a mixture of 780 μL isopropanol and 200 μL deionized water, and 20 μL 5 wt% Nafion solution was added. Ultrasonication was performed for 1 h. 10 μL of the dispersed slurry (ink) was dripped onto a disk (0.2475 cm 2 ) electrode, and fully dried under a baking lamp to make 40ug Pt cm -2 Electrode head with catalyst loading for testing. The specific electrochemical characterization test was carried out in a standard three-electrode system, with a carbon rod as the counter electrode and a saturated calomel electrode as the reference electrode. The test was carried out at room temperature, and the ORR polarization curve was measured in an O2-saturated 0.1M HClO4 electrolyte, and the background CV curve was measured in a N2-saturated 0.1M HClO4 electrolyte. The specific scanning potential was 0.1-1.1 VRHE, and the scanning rate was 10 mV s -1 .

[0133] Figure 1 This is the XRD pattern of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1. It can be seen that N,S-PtCo / C is a standard intermetallic ordered alloy, which corresponds one-to-one with the standard comparison card.

[0134] Figure 2 TEM image and particle size statistical distribution of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1. It can be seen from the figure that the binary N, S-PtCo / C intermetallic ordered alloy nanoparticles are uniformly dispersed on the doped carbon carrier with an average particle size of 3.5 nm. The particles are highly dispersed and uniform.

[0135] Figure 3The activity comparison diagram of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1, commercial Pt / C (Comparative Example 5), and PtCo / C (Comparative Example 6) shows that the mass specific activity of Example 1 is 0.813AmgPt -1 , respectively commercial Pt / C (0.18AmgPt -1 ) is 4.5 times higher than commercial PtCo / C (0.43AmgPt -1 ). This indicates that the ORR performance of N and S co-doped PtM / C alloy is high.

[0136] Figure 4 ORR forward scanning polarization curves of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1 in an O2-saturated 0.1M HClO4 solution at the initial stage and after 30,000 cycles of stability testing, Figure 5 The cyclic voltammetry curves of the initial and 30,000-cycle stability test of the nitrogen-sulfur dual-doped PtM / C catalyst of Example 1. Among them, Initial corresponds to the initial state, and After30K corresponds to the state after 30,000 cycles. It can be seen from the figure that its initial ORR half-wave potential is 0.95V. After 30,000 cycles of accelerated decay, the half-wave potential only decays by 8mV, and the area specific activity (SA) decays by 12.7%. The ECSA does not change much after 30,000 cycles of accelerated decay, and the mass specific activity (MA) changes from 0.813Amg Pt -1 Down to 0.742Amg Pt -1 , attenuated by 8.7%, and the excellent ORR performance of the catalyst was much higher than the requirements of the DOE 2025 target. This is due to the synergistic effect of the N and S elements in the catalyst, which can make the metal atoms evenly and fully dispersed on the carbon carrier, inhibit the agglomeration of Pt nanoparticles, and anchor the alloy nanoparticles; at the same time, the doping of transition metals and N or S in the catalyst produce a synergistic effect, which can reduce the surface energy of Pt atoms on the surface of nanoparticles and inhibit the dissolution of Pt and M atoms during the ORR reaction.

[0137] Fig. 6A and Figure 6B They are the XRD and ORR forward scanning polarization curves of Control Example 1, respectively.

[0138] Fig. 7A and Figure 7B They are the XRD and ORR forward scanning polarization curves of Control Example 2, respectively.

[0139] Fig. 8A and Figure 8B They are the XRD and ORR forward scanning polarization curves of Control Example 3 respectively.

[0140] Fig. 9A and Fig. 9BThey are the XRD and ORR forward scanning polarization curves of Control Example 4, respectively.

[0141] Furthermore, the effect of organic small molecule ligands on the catalyst in aqueous synthesis was explored. Using Example 1 as a standard sample, the organic small molecule ligand added in step (1) was eliminated, and the comparative example 1 was synthesized. Its particle size was very large, 9.9 nm, and the particles showed obvious agglomeration. Its mass specific activity at 0.9 V was 0.354 AmgPt -1 , the particles agglomerate and are not suitable for actual fuel cells. This comparison shows that the addition of organic small molecule ligands has a regulatory effect on the catalyst particle size and activity.

[0142] In order to understand the effect of N and S element doping alone, two groups of experiments were conducted, namely, control examples 2 and 3. In step (1), only sodium glutamate, a small molecule ligand containing N element, was added to synthesize control example 2, and its particle size was 5.1 nm. In the RDE performance test, the mass specific activity of control example 2 at 0.9 V was 0.572AmgPt -1 . This comparison shows that the addition of N element helps to regulate the catalyst particle size, activity, etc., but its particle size and activity are not as suitable as those of Example 1 in terms of the actual fuel cell application. This shows that the addition of organic small molecule ligands containing only N element has limited control over the catalyst particle size. In addition, in step (1), only sodium thioglycolate, a small molecule ligand containing S element, is added to synthesize Control Example 3, and its particle size is 4.4 nm, which is moderate. However, its mass specific activity at 0.9 V is 0.429Amg Pt -1 , the performance is not as good as Example 1 and Control Example 2 in terms of suitability for actual fuel cell applications. This comparison shows that the addition of S alone helps to regulate the catalyst particle size, but the ability to regulate the catalyst performance is insufficient. In summary, only the doping of N and S elements can synchronously regulate the particle size and performance of the catalyst.

[0143] In addition, in order to understand whether the doping method of organic small molecule ligands has an effect on the catalyst, a control example 4 was prepared, in which N and S elements were doped on the carbon support. The catalyst particle size of the synthesized control example 4 was 6.1 nm, and the mass specific activity of 0.9 V was 0.486 Amg Pt -1 This comparison shows that the doping position of N and S elements has an important influence on the particle size and performance regulation of the catalyst. Only by doping them between particles rather than doping them on the carbon carrier in advance can the agglomeration of nanoparticles be better suppressed and the catalyst performance be improved.

[0144] Table 2 is a comparison of the mass specific activity, area specific activity and ECSA data at 0.9 V vs. RHE after the first cycle and 30,000 cycles of stability testing of Example 1.

[0145] Table 2

[0146]

[0147] In summary, the nitrogen-sulfur co-doped PtM / C catalyst prepared by the method of the present invention has high electrochemical ORR performance and stability, among which the initial mass specific activity of PtCo / C can reach 0.813AmgPt -1 After 3w cycles of stability testing, the mass specific activity decreased by 8.7%, and the performance was better than that of commercial platinum-carbon / platinum-cobalt binary alloys, and the activity and stability reached the DOE2025 target.

[0148] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for synthesizing a nitrogen-sulfur dual-doped PtM / C catalyst, characterized in that: The synthesis method comprises the following steps: (1) mixing an organic ligand, a noble metal Pt precursor, an M precursor and a carbon support with a non-organic solvent, and drying to obtain a catalyst precursor; Wherein, M in the M precursor is a transition metal element, and the organic ligand includes a doping element, and the doping element includes N and S; (2) The catalyst precursor is subjected to a first calcination in a reducing atmosphere to obtain a nitrogen-sulfur dual-doped PtM / C catalyst.

2. The method for synthesizing the nitrogen-sulfur dual-doped PtM / C catalyst according to claim 1, characterized in that: The organic ligand in step (1) comprises at least one of pyroglutamic acid, sodium pyroglutamate, histidine, valine, aspartic acid, sodium aspartate, threonine, theanine, serine, citrulline, glycine, sodium glycinate, glutamic acid, sodium glutamate, sodium thioglycolate, thiolactic acid, cysteine, hexylthioamide, pentylthioamide, dithiothreitol and 1-thioglycerol, preferably a small molecule organic ligand; Preferably, the small molecule organic ligand comprises at least one of sodium glycine, sodium glutamate, cysteine, sodium thioglycolate and thiolactic acid; Preferably, the molar ratio of the organic ligand in step (1) to the noble metal element in the noble metal Pt precursor is 1:(0.5-2), preferably 1:(1-1.5).

3. The method for synthesizing the nitrogen-sulfur dual-doped PtM / C catalyst according to claim 1 or 2, characterized in that: The non-organic solvent in step (1) is water; Preferably, the noble metal Pt precursor in step (1) is a Pt precursor; Preferably, the Pt precursor includes at least one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride, tetraammine platinum nitrate and potassium hexaiodide platinate; Preferably, the transition metal element M is selected from at least one of Fe, Co, Ni, Cu and Zn; Preferably, the M precursor in step (1) comprises at least one of ferric nitrate, ferric sulfate, ferric chloride, cobalt nitrate, cobalt sulfate, cobalt chloride, nickel nitrate, nickel sulfate, nickel chloride, copper nitrate, copper sulfate, copper chloride zinc nitrate, zinc sulfate and zinc chloride; Preferably, the molar ratio of the noble metal Pt to the transition metal M is (1.2-1):

1.

4. The method for synthesizing the nitrogen-sulfur co-doped PtM / C catalyst according to any one of claims 1 to 3, characterized in that: The mixing in step (1) is carried out under stirring, and the mixing time is 3-48 hours, preferably 10-18 hours; Preferably, the drying method in step (1) is: removing water by rotary evaporation and then performing vacuum drying.

5. The method for synthesizing the nitrogen-sulfur co-doped PtM / C catalyst according to any one of claims 1 to 4, characterized in that: Step (2) the first calcination time is 2-10h; Preferably, the heating rate of the first calcination in step (2) is 1-10°C / min; Preferably, the temperature of the first calcination in step (2) is 600-950°C; Preferably, the gas in the reducing atmosphere in step (2) comprises reducing gas and protective gas, and the volume concentration of the reducing gas is 2-10%.

6. The method for synthesizing the nitrogen-sulfur dual-doped PtM / C catalyst according to any one of claims 1 to 5, characterized in that: The synthesis method further comprises performing step (3) after the first calcination: The product obtained by the first calcination is acid-washed, dried, and then subjected to a second calcination in a reducing atmosphere to obtain a doped PtM / C catalyst.

7. The method for synthesizing the nitrogen-sulfur dual-doped PtM / C catalyst according to claim 6, characterized in that: In step (3), the acid used for pickling includes at least one of perchloric acid, sulfuric acid, nitric acid and acetic acid; Preferably, in step (3), the concentration of the acid used in the pickling is 0.1-0.5M; Preferably, in step (3), the pickling temperature is 50-80°C; Preferably, in step (3), the pickling time is 0.5-4h; Preferably, in step (3), the second calcination time is 0.5-4h; Preferably, in step (3), the heating rate of the second calcination is 1-10°C / min; Preferably, in step (3), the temperature of the second calcination is 200-500°C; Preferably, in step (3), the gas in the reducing atmosphere includes reducing gas and protective gas, and the volume concentration of the reducing gas is 2-10%.

8. A nitrogen-sulfur co-doped PtM / C catalyst prepared by the method according to any one of claims 1 to 7, characterized in that: The nitrogen-sulfur dual-doped PtM / C catalyst includes a carbon carrier and a platinum-based binary alloy supported on the carbon carrier. The platinum-based binary alloy is an intermetallic ordered alloy formed by a precious metal element Pt and a transition metal element M. The platinum-based binary alloy is doped with doping elements, and the doping elements include N and S.

9. The nitrogen-sulfur co-doped PtM / C catalyst according to claim 8, characterized in that: The mass percentage of the precious metal element Pt in the doped PtM / C catalyst is 10-50wt%, preferably 25-35wt%; Preferably, the transition metal element M accounts for 3-30wt% by weight in the doped PtM / C catalyst, preferably 6-10wt%; Preferably, the transition metal element M is selected from at least one of Fe, Co, Ni, Cu and Zn; Preferably, the mass proportion of the doping element in the nitrogen-sulfur dual-doped PtM / C catalyst is 0.1-5wt%, preferably 0.5-1%; Preferably, the doping element is uniformly doped in the lattice of the binary alloy nanoparticles in the form of single atoms; Preferably, the average particle size of the binary alloy is 3-8 nm.

10. A fuel cell, characterized in that: The fuel cell comprises the nitrogen-sulfur dual-doped PtM / C catalyst as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Catalyst for fuel cell and preparation method thereof

    CN111224116A

Cited By

  • Ternary platinum-based ordered alloy catalyst, preparation method thereof and fuel cell

    CN120690876A

  • Ligand modified platinum-carbon catalyst as well as preparation method and application thereof

    CN120878870A